A Reflective Entrepreneur: Ashok Vasudevan and the Journey of Tastybite. (April 2022) - Shankar, Raj K.; Gopalakrishnan, Shanthi
The literature on entrepreneurship acknowledges that entrepreneurs are both thinkers and doers. While scholars have previously explored entrepreneurs' cognitions and actions, research on entrepreneurs' reflective practices remains limited. To stimulate greater scholarly attention on exploring entrepreneurs as reflective practitioners, in this 'Meet the Person' article we build on two interviews with the celebrated entrepreneur Ashok Vasudevan. From buying the venture off Unilever and eventually selling it to Mars, Ashok's journey reflects an entrepreneur's struggles in growing a venture from an emerging economy (India of the 90s). Tearing down entrepreneurship literature's stereotypical and mythological lore, Ashok's journey with Tasty Bite is also a case of why "the" theory of entrepreneurship continues to remain elusive. Three key themes from Ashok's journey (failure, sustainability, and exit) help highlight the rich possibilities that reflective practice offers to entrepreneurship literature. Implications for the advancement of reflective practice in entrepreneurship research, education, and practice are presented.